2022
DOI: 10.3389/fpsyt.2022.1041829
|View full text |Cite
|
Sign up to set email alerts
|

Effects and safety of auricular acupressure on depression and anxiety in isolated COVID-19 patients: A single-blind randomized controlled trial

Abstract: ObjectivePsychological distress such as depression and anxiety resulted from coronavirus disease 2019 (COVID-19) have attracted increasing attention. The aim of this randomized controlled trial is to evaluate the effects and safety of auricular acupressure on depression and anxiety in isolated COVID-19 patients.Methods68 participants diagnosed with COVID-19 pneumonia (18–80 years old, SDS ≥ 50, SAS ≥ 45) were recruited and randomly allocated to the auricular acupressure group and the sham auricular acupressure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…Four studies (8,11,14,15) selectively report results, indicating in a high risk of bias. Other studies (20,23,(36)(37)(38)40) had registered online with specified outcomes, leading to a low risk of bias in selective reporting. All trials had an unknown risk in other sources of bias.…”
Section: Quality Critical Appraisalmentioning
confidence: 99%
“…Four studies (8,11,14,15) selectively report results, indicating in a high risk of bias. Other studies (20,23,(36)(37)(38)40) had registered online with specified outcomes, leading to a low risk of bias in selective reporting. All trials had an unknown risk in other sources of bias.…”
Section: Quality Critical Appraisalmentioning
confidence: 99%
“…Acupoint stimulation has promising applications in improving psychiatric symptoms, such as anxiety and depression in patients with long COVID. A single-blind, randomized controlled study showed that auricular acupressure in the area of hypodermic, subcortex, hepatic, and endocrine may alleviate anxiety and depression in patients with COVID-19 [99] . In addition, taVNS may improve immune function through the cholinergic anti-inflammatory pathway and modulate brain circuits through the hypothalamic-pituitary-adrenal axis [100] .…”
Section: Acupoint Stimulation May Relieve Other Symptoms Of Long Covidmentioning
confidence: 99%
“…[11][12][13][14][15][16][17][18][19] Acupuncture at acupoints and auricular acupressure can treat a variety of disorders, such as neck pain, neuropathic pain, stroke rehabilitation, Alzheimer disease, Parkinson disease, dysmenorrhea, depression and anxiety. [14,16,[20][21][22][23][24][25] Most importantly, they have also been reported to effectively manage myopia. [26,27] However, data on the management of APP plus acupuncture in JPM are limited.…”
Section: Introductionmentioning
confidence: 99%